2022
DOI: 10.1007/s13304-022-01372-9
|View full text |Cite
|
Sign up to set email alerts
|

Primary angioembolization in liver trauma: major hepatic necrosis as a severe complication of a minimally invasive treatment—a narrative review

Abstract: The liver is the second most commonly solid organ injured in blunt abdominal trauma. Liver injuries are classified according to the American Association for the Surgery of Trauma Injury Scale. The choice of Non-Operative Management is based on generalized clinical patients’ conditions combined with the evidence on CT scan imaging. To date, there are no consensus guidelines on appropriate patient selection criteria for those who would benefit from angiography and angioembolization. Major hepatic necrosis is a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…One study has found major hepatic necrosis in up to 63% of patients who underwent embolization, which correlated with grade of liver injury. Several other studies have also demonstrated hepatic necrosis rates increasing with higher grades of injury 19–21 …”
Section: Algorithmmentioning
confidence: 93%
See 1 more Smart Citation
“…One study has found major hepatic necrosis in up to 63% of patients who underwent embolization, which correlated with grade of liver injury. Several other studies have also demonstrated hepatic necrosis rates increasing with higher grades of injury 19–21 …”
Section: Algorithmmentioning
confidence: 93%
“…15,16,18,19 One study has found major hepatic necrosis in up to 63% of patients who underwent embolization, which correlated with grade of Several other studies have also demonstrated hepatic necrosis rates increasing with higher grades of injury. [19][20][21] Biliary complications can occur in up to 22% of patients after angioembolization. However, such complications are not always specific to angioembolization and can occur in up to 30% in patients with hepatic trauma managed without embolization, either operative or nonoperative.…”
Section: Nonoperative Managementmentioning
confidence: 99%
“…Segalini et al, in their review of TAE hemostasis for liver trauma, reported that MHN occurred in 16% of cases. 1 In this case, hepatic necrosis of the posterior section occurred after TAE hemostasis for hemorrhage associated with blunt hepatic trauma. Traumatic occlusion of the posterior portal vein appeared to be the reason for necrosis after TAE.…”
Section: Discussionmentioning
confidence: 77%
“…Small areas of hepatic necrosis following TAE for trauma are often experienced. Segalini et al, in their review of TAE hemostasis for liver trauma, reported that MHN occurred in 16% of cases 1 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation